Maternal Factor Dppa3 Activates 2C-Like Genes and Depresses DNA Methylation in Mouse Embryonic Stem Cells - Zhang, Chuanyu; Wen, Hang; Liu, Siying; Fu, Enze; Yu, Lu; Chen, Shang; Han, Qingsheng; Li, Zongjin; Liu, Na (Frontiers in Cell and Developmental Biology, 2022)
Mouse embryonic stem cells (ESCs) contain a rare cell population of ‘2-cell embryonic like’ cells (2CLCs) that display similar features to those found in the 2-cell (2C) embryo and thus represent an in vitro model for studying zygotic genome activation (ZGA) progress. However, the positive regulators determinants of 2CLCs conversion and ZGA have not been completely elucidated. Here we identify a new regulator promoting 2CLCs and ZGA transcripts. Through a combination of overexpression (OE), knockdown (KD), together with transcriptional analysis and methylome analysis, we find that Dppa3 regulates the 2CLCs associated transcripts, DNA methylation, and 2CLCs population in ESCs. The differentially methylated regions (DMRs) analysis identified 6920 (98.2%) hypomethylated, whilst only 129 (1.8%) hypermethylated, regions in Dppa3 OE ESCs, suggesting that Dppa3 facilitates 2CLCs reprogramming. The conversion to 2CLCs by overexpression of Dppa3 is also associated with DNA damage response. Dppa3 knockdown manifest impairs transition into the 2C-like state. Global DNA methylome and chromatin state analysis of Dppa3 OE ESCs reveal that Dppa3 facilitates the chromatin configuration to 2CLCs reversion. Our finding for the first time elucidates a novel role of Dppa3 in mediating the 2CLCs conversion, and suggests that Dppa3 is a new regulator for ZGA progress.